Osas incidence in septal deviation Mladina type 7 (Annals of Medical Research, 2023)
Aim: Obstructive sleep apnea syndrome (OSAS) is a disease that progresses with attacks of upper respiratory tract obstruction during sleep, causing recurrent hypoxia as a result. These obstructions usually occur due to mechanical (septum deviation, concha bullosa, concha hypertrophy) or inflammatory (acute/chronic rhinitis) causes and pose a risk for OSAS. Therefore, clinical and radiographic findings guide the diagnosis of the disease. Among the radiographic examinations, the most common, thin-section paranasal computed tomography (CT) is used for determining the obstruction site and preoperative treatment planning. In this study, we aimed to investigate the paranasal BT findings of OSAS patients.Materials and Methods: Patients with OSAS were included in the study. Seven hundred seventy-seven patients whose paranasal CT results were registered in the hospital information system and met the inclusion criteria were included in the study. Results: When the patients were evaluated according to the paranasal CT findings, the most common finding was deviation of the septum, followed by the agger nasi cells.  Type 7 deviation according to Mladina  classification in OSAS was significantly higher than simple snoring and type 1 deviation in mild OSAS was significantly higher than moderate-severe OSAS (p